Penerapan Nilai-Nilai Pancasila dalam Pembelajaran PKN di Sekolah Dasar - Nurlaila; Shofi Nur Amalia (Advances In Education Journal, 2026)
Pancasila is the foundation of the state and the guiding principle of the Indonesian nation, and it must be instilled in students from an early age, particularly in elementary schools. Civics Education (PKn) plays a crucial role in instilling Pancasila values through the learning process. Civics learning aims to shape students’ knowledge, attitudes, and behaviors that reflect the values of divinity, humanity, unity, democracy, and social justice. The application of Pancasila values in Civics learning is carried out in stages and simply through prayer, tolerance among students, group cooperation, class discussions, and the cultivation of fairness and responsibility. Furthermore, teacher role models and school activities such as mutual cooperation (gotong royong) strengthen the practice of Pancasila values. In the era of globalization, Civics learning is an important means of fostering a sense of nationalism and maintaining national identity. Through Civics learning in elementary schools, it is hoped that students will grow into a generation with Pancasila-based character and love for their homeland.